Toponyms as an exclusionary feature: an analysis on the names of avenues, streets and side streets in the city of Oeiras, state of Piauí - Santana, Messias dos Santos; Moura, Layane Albuquerque de (Linha D’Água, 2023)
The study of proper names is an important access to social and historical aspects that link the present to the past. It also contributes to understanding the connection between them. This research focuses on street names of Oeiras city, state of Piauí, aiming at i) presenting the main motivating factors of such toponymic spaces; ii) identifying the main social and political omissions in the designations of such urban spaces; iii) and establishing the social and historical facts under the denominative process. In order to achieve these goals, 33 maps of local census with respective descriptions, reported by IBGE, in 2010, were analyzed. The results indicated that the names of avenues, streets, and side streets are mainly antropocultural toponyms. As a result, it was evident that the streets named after an anthroponym mostly honor men of privileged classes that performed socially, historically and culturally privileged professions.